Analisis Aspek Manajemen dan Aspek Pemasaran Toko Bangunan Ulin Utama - Fayziah Aulia Husna; Rahmah Rahmah; Rahma Aulia; Muhammad Firliadi Noor Salim (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Toko Ulin Utama is a building materials store located in Kandangan Hulu, Hulu Sungai Selatan Regency, South Kalimantan. Along with the development of this region, the demand for building materials continues to increase, in line with the growth of infrastructure and the property sector. This condition makes Toko Ulin Utama one of the key suppliers that plays an important role in supporting development activities in the area. This study focuses on two main aspects: management and marketing. In terms of management, the focus is on how the store manages human resources, organizes its structure, and improves operational efficiency. Meanwhile, in terms of marketing, this research discusses promotion strategies, market segmentation, consumer behavior, and the store's competitiveness in the local market. The data for this research was obtained through direct interviews with the store owner and manager, providing in-depth information about the strengths, weaknesses, opportunities, and challenges faced by the store in its operations. The concept guiding this study is the business feasibility study, which explores various aspects such as market, marketing, and management. The results of this study are expected to provide a clear picture of the operational feasibility of Toko Ulin Utama, while also serving as a guide to developing more effective and sustainable business strategies. With the increasing demand for building materials driven by the development of infrastructure and the property sector in the area, the findings of this study are expected to help the store take advantage of market opportunities and better address existing challenges.